PERANAN MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT KOZA PRESISI INDONESIA KOTA TANGERANG - Pusporini Palupi Jamaludin (Jurnal Ilmiah Ekonomi Bisnis, 2021)
Abstract: PT. Koza Presisi Indonesia is a company engaged in automotive manufacturing services, namely in the machining process. This study aims to review in terms of the role of work motivation in improving employee performance at PT. Koza Presisi Indonesia. This study uses a descriptive qualitative approach with an interpretive approach in analyzing data with literature review. Collecting and processing data are also carried out by means of observation, interviews, documentation and triangulation. This research uses structured interviews. The sample in this study amounted to 16 people (15 people as the main informant and 1 person as triangulation). The sample was selected with the following characteristics: male and female, 3-5 years of age, education and willingness to be informants. Samples in qualitative research are not named as respondents but as sources, participants, and informants. From the research results, it is known that the level of employee motivation is still not good overall so that the role of motivation to improve employee performance is still not optimal. However, to increase motivation was expressed by key informants by maintaining harmony with employees, building a good working atmosphere, and accommodating complaints from subordinates to be evaluated. Key informants revealed to improve employee performance by establishing familiarity with employees, and consulting with team leaders about the problems that occur. However, he also revealed that he would create a system such as giving rewards and training as a form of performance improvement. Keyword : Work Motivation, Employee Performance